Intensidade amostral e ciclagem de nutrientes em serapilheira e necromassa em sistemas ILPF - Souza, Emanuella Farias Santos (2022)
The search for sustainable development is an increasingly present theme in agriculture, where the process of modernization and incorporation of new technologies brought crop-livestock-forest integration (ICLF) as an alternative to the balance of agricultural, livestock and forestry production activities in the same production unit. To evaluate the potential of this system to sequester and stock carbon, it is necessary to determine the total forest biomass. Litter and necromass present in this ecosystem comprise a significant fraction in carbon storage capacity, but we do not know what sampling effort is necessary to quantify litter and necrosass in ICLF systems. Directing the elaboration of a method that considers the particularities of each system, regarding the thinning management performed in ICLF’s. The treatments evaluated with the cultivation of Eucalyptus urograndis, clone H13, were ICLF-S: eucalyptus ICLF in simple lines (3 m x 37 m), ILF-T: Eucalyptus ILF in triple line strips (3'(3.5 m x 6 m) + 30 m) and H: homogeneous eucalyptus planting as a control (3.5 m x 3 m). The experimental design was randomized blocks with three replications. For litter collection, plots were installed where sampling grids of 0,25 m2 and simulated grids of 1m2 were installed. The necromass was sampled using the intercept line method. It was found that ICLF requires greater sampling effort to quantify litter and necromass, and the sampling effort is higher in the system maintained with triple renque after thinning. It was determined that it is feasible to assume the sample intensity assuming error of up to 20%, in which it is possible to reduce the sampling effort without impairment in experimental accuracy. The sampling intensity for the sampling grid of 0,25 m² is 21 simple samples for ILF-T, 12 for ICLF-S and 5 for H. And for the 1 m² grid, the sampling intensity is 12 simple samples for the ILF-T, 7 for the ILPF-S and 4 for the H. The random or systematic litter collection method does not influence the sampling effort. ICLF demands greater sampling intensity to quantify necromass, compared to homogeneous planting. Being necessary 59 simple samples for the IPFT, 40 for the ICLF-S and 14 for the H. Subsequently, the nutrient stock of these compartments was evaluated, in the effective area of the rows and in the total area of the system. There was no difference in C stock in the ICLF’s row area, even after thinning management. The order of litter nutrient content in the integrations was C > Ca > N > K > Mg > P > S, while in the homogeneous planting, C > Ca > N > Mg > K > P > S, differentiating the order from the stock of K and Mg. ICLF does not change the order of micronutrients stock, maintaining (Fe > Mn > B > Zn). To understand the eucalyptus litter decomposition process in ICLF systems, we evaluated the decomposition dynamics and the rate of nutrient release from the leaves. The ICLF systems showed different behaviors for litter decomposition in both seasons. In the dry period, the rate of decomposition and release of nutrients was slow, with a longer halflife. The decomposition rate was lower in the ICLF’s and the ILF-T had a higher decomposition rate in relation to the ICLF-S. In the rainy season, the ICLF increased the decomposition rate and reduced the half-life. ILF -T had a higher decomposition rate and a shorter half-life in the rainy season.